Here's the question you clicked on:

55 members online
  • 0 replying
  • 0 viewing

mitchelsewbaran

  • 3 years ago

Simplify f(x) =(2x^2+3x+1)/(2x+1). Using complete sentences, explain why f(1) = 2, f(0) = 1, and f(-1) = 0, yet f(-1/2) is undefined. Be sure to show your work.

  • This Question is Closed
  1. gerryliyana
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 2

    (2x^2+3x+1)/(2x+1). (2x+1) (x + 1)/(2x+1) (x+1)

  2. gerryliyana
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 2

    So, f(x) = (x+1) if there is f(1) then replace x by 1 and further

  3. gerryliyana
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 2

    for..., let see explain why f(1) = 2,??? because f(x) = x + 1 f(1) = 1 + 1 f(1) = 2

  4. Not the answer you are looking for?
    Search for more explanations.

    • Attachments:

Ask your own question

Sign Up
Find more explanations on OpenStudy
Privacy Policy